Two-State Exchange Dynamics in Membrane-Embedded Oligosaccharyltransferase Observed in Real-Time by High-Speed AFM. Issue 22 (6th November 2020) - Kawasaki, Yuki; Ariyama, Hirotaka; Motomura, Hajime; Fujinami, Daisuke; Noshiro, Daisuke; Ando, Toshio; Kohda, Daisuke
Abstract: Oligosaccharyltransferase (OST) is a membrane-bound enzyme that catalyzes the transfer of oligosaccharide chains from lipid-linked oligosaccharides (LLO) to asparagine residues in polypeptide chains. Using high-speed atomic force microscopy (AFM), we investigated the dynamic properties of OST molecules embedded in biomembranes. An archaeal single-subunit OST protein was immobilized on a mica support via biotin–avidin interactions and reconstituted in a lipid bilayer. The distance between the top of the protein molecule and the upper surface of the lipid bilayer was monitored in real-time. The height of the extramembranous part exhibited a two-step variation with a difference of 1.8 nm. The high and low states are designated as state 1 and state 2, respectively. The transition processes between the two states fit well to single exponential functions, suggesting that the observed dynamic exchange is an intrinsic property of the archaeal OST protein. The two sets of cross peaks in the NMR spectra of the protein supported the conformational changes between the two states in detergent-solubilized conditions. Considering the height values measured in the AFM measurements, state 1 is closer to the crystal structure, and state 2 has a more compact form. Subsequent AFM experiments indicated that the binding of the sugar donor LLO decreased the structural fluctuation and shifted the equilibrium almost completely to state 1. This dynamic behavior is likely necessary for efficient catalytic turnover. Presumably, state 2 facilitates the immediate release of the bulky glycosylated polypeptide product, thus allowing OST to quickly prepare for the next catalytic cycle. Graphical Abstract: Unlabelled Image Highlights: Oligosaccharyltransferase catalyzes the asparagine-linked glycosylation of proteins. AFM revealed a dynamic two-state exchange in height in a lipid bilayer environment. NMR revealed a slow conformational change between two states in detergent micelles. This dynamic behavior is considered necessary for efficient catalytic turnover.